Handbook of Statistical Genetics 2007
DOI: 10.1002/9780470061619.ch30
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics

Abstract: This chapter reviews some of the statistical methodologies used in the genetic analysis of endangered and managed populations. The topics covered include the estimation of effective population size, N e , the detection of past changes in population size, the estimation of admixture proportions, and the analysis of local population structure, kinship, and relatedness through genotypic methods. The reasons why it may be useful to measure N e are discussed. Using genetic information it is possible to estimate N e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 113 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…While this effect has been known from a theoretical point of view (Wakeley 1999;Beaumont 2003bBeaumont , 2004; Nielsen and Beaumont 2009), it had not been quantified for data sets simulated with different levels of gene flow and diversity. We found that the effect was limited when genetic differentiation was low but that it could be observed for values of F ST that are typically reported in the literature (e.g., Gonc xalves et al 2009;Holsinger and Weir 2009;Quéméré et al 2009;Rosel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While this effect has been known from a theoretical point of view (Wakeley 1999;Beaumont 2003bBeaumont , 2004; Nielsen and Beaumont 2009), it had not been quantified for data sets simulated with different levels of gene flow and diversity. We found that the effect was limited when genetic differentiation was low but that it could be observed for values of F ST that are typically reported in the literature (e.g., Gonc xalves et al 2009;Holsinger and Weir 2009;Quéméré et al 2009;Rosel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In general all models follow the same basic assumptions: the focal population is expected to be in panmixia, discrete generations exist and mutation, selection and migration are negligible compared to genetic drift, thus representing a simplified Wright-Fisher population [ 30 , 31 ]. Short-term N e estimators are based on the variance of allele frequency changes over time and hence provide a harmonic mean of N e for the time elapsed between the two sampling periods (for comprehensive reviews see [ 60 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellite markers have been widely used to study individual identification, phylogeographic relationships, and genetic variation, as well as population structuring and genetic differentiation of various wildlife species (Beaumont and Bruford, 1999;Polziehn et al, 2000;Hu et al, 2007;Lee et al, 2011;Park et al, 2011). Although plentiful ecological studies and some phylogenetic research with mitochondrial DNA on raccoon dog have been conducted, there are no previous data on the population structure using microsatellite markers (Kahula and Saeki, 2004).…”
Section: Introductionmentioning
confidence: 99%